Challenges in Islamic Religious Education Learning in Schools: Solutions and Resolution Strategies - Muhamad Nazari Hauqal; Fauzan; Alfi Lutfiyah (Yayasan Azhar Amanaa Yogyakarta, 2026)
Islamic Religious Education (IRE) learning in schools plays a strategic role in shaping students' character and morals. However, in practice, IRE learning faces various complex and multidimensional challenges. This article aims to identify and analyze the multiple challenges encountered in IRE learning in schools, covering the aspects of teachers, students, curriculum, infrastructure, learning methods, and the environment. The method used is a literature review (library research) by analyzing various relevant sources. The results indicate that the challenges in IRE learning stem from both internal and external factors. Internal factors include sub-optimal teacher competence, low student learning motivation, and a superficial understanding of religion. External factors encompass a dense curriculum, limited infrastructure, the negative influence of social media, and an unsupportive family environment. Synergy among schools, families, and communities, alongside the renewal of learning methods and approaches, is required to overcome these challenges.